A Survey Of Art Learning In Kindergarten During The Covid 19 Pandemic - Joko Pamungkas; Amir Syamsudin; Harun Ar Rosid (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study was to describe the practice of art learning in Kindergarten during the COVID-19 pandemic. The research method used was a survey. The research target is that a detailed description of art learning practices in Kindergarten during the COVID-19 pandemic can be drawn up as a basis for formulating the basic needs for improving the quality of learning. The results of the research can be used to improve educational praxis, formulate hypotheses, create initial development plans, evaluate programs, and evaluate policies, especially art learning in Kindergarten units. The results showed that PAUD teachers developed an art lesson plan and implemented it. However, the type of art that was taught was visual art, while dance and music were never performed. Likewise, the use of WhatsApp media is more widely used in online art learning than other social media. Also using audio media and taking examples of art learning from social media. Parents actively participate in taking learning media to school and sending photos and videos of the learning process at home. With online learning, teachers have difficulty using technology for early childhood art learning, and prefer to use face-to-face learning. Likewise with parents, parents prefer their children to learn face to face so they can meet the teacher directly.